SPARCL1 Influences Bovine Skeletal Muscle-Derived Satellite Cell Migration and Differentiation through an ITGB1-Mediated Signaling Pathway - Yuxin Wang; Shuaiyu Liu; Yunqin Yan; Shufeng Li; Huili Tong (Animals, 2020)
As an extracellular matrix protein, secreted protein acidic and rich in cysteine (SPARC)-like 1 (SPARCL1) is involved in various cell functions. It was previously implicated in bovine skeletal muscle-derived satellite cell (MDSC) differentiation; however, the underlying mechanism remains unknown. In this study, immunoprecipitation and mass spectrometry revealed that integrin β1 (ITGB1) combines with SPARCL1. Further, co-immunoprecipitation demonstrated that SPARCL1 interacts with ITGB1. Cell scratch assays explored the influence of SPARCL1 on MDSC migration through ITGB1. In addition, desmin staining for myotube fusion rate and MyoD protein expression results showed that SPARCL1 promotes MDSC early differentiation through ITGB1. Furthermore, Western blotting results demonstrated that SPARCL1 regulates the expression of p-FAK, p-paxillin, vinculin, Cdc42, and Arp2/3 through ITGB1. These findings indicate that SPARCL1 may influence bovine MDSC migration and differentiation through an ITGB1-mediated cell signaling pathway. Herein, we elucidated the mechanism through which SPARCL1 affects MDSC differentiation. Our results provide insight into the molecular mechanism of muscle development and may in the future facilitate skeletal muscle regeneration and treatment.